Shadow and substance: Eucharistic controversy and English drama across the Reformation divide - Zysk, Jay (Reformations: medieval and early modern, 2017)
"Shadow and Substance is the first book to present a sustained examination of the relationship between Eucharistic controversy and English drama across the Reformation divide. In this compelling interdisciplinary study, Jay Zysk contends that the Eucharist is not just a devotional object or doctrinal crux, it also shapes a way of thinking about physical embodiment and textual interpretation in theological and dramatic contexts. Regardless of one's specific religious identity, to speak of the Eucharist during that time was to speak of dynamic interactions between body and sign. In crossing periodic boundaries and revising familiar historical narratives, Shadow and Substance challenges the idea that the Protestant Reformation brings about a decisive shift from the flesh to the word, the theological to the poetic, and the sacred to the secular. The book also adds to studies of English drama and Reformation history by providing an account of how Eucharistic discourse informs understandings of semiotic representation in broader cultural domains. This bold study offers fresh, imaginative readings of theology, sermons, devotional books, and dramatic texts from a range of historical, literary, and religious perspectives. Each of the book's chapters creates a dialogue between different strands of Eucharistic theology and different varieties of English drama. Spanning England's long reformation, these plays--some religious in subject matter, others far more secular--reimagine semiotic struggles that stem from the controversies over Christ's body at a time when these very concepts were undergoing significant rethinking in both religious and literary contexts. Shadow and Substance will have a wide appeal, especially to those interested in medieval and early modern drama and performance, literary theory, Reformation history, and literature and religion"--